Investigating the occurrence of autoimmune diseases among children and adolescents hospitalized for Mycoplasma pneumoniae infections - Ha, Eun Kyo; Kim, Ju Hee; Cha, Hye Ryeong; Han, Bo Eun; Shin, Youn Ho; Baek, Hey-Sung; Choi, Sun Hee; Han, Man Yong (Frontiers in Immunology, 2023)
Background: Mycoplasma pneumoniae infection is common in the general population and may be followed by immune dysfunction, but links with subsequent autoimmune disease remain inconclusive.Objective: To estimate the association of M. pneumoniae infection with the risk of subsequent autoimmune disease.Methods: This retrospective cohort study examined the medical records of South Korean children from January 1, 2002 to December 31, 2017. The exposed cohort was identified as patients hospitalized for M. pneumoniae infection. Each exposed patient was matched with unexposed controls based on birth year and sex at a 1:10 ratio using incidence density sampling calculations. The outcome was subsequent diagnosis of autoimmune disease, and Hazard ratios (HRs) were estimated with control for confounders. Further estimation was performed using hospital-based databases which were converted to a common data model (CDM) to allow comparisons of the different databases.The exposed cohort consisted of 49,937 children and the matched unexposed of 499,370 children. The median age at diagnosis of M. pneumoniae infection was 4 years-old (interquartile range, 2.5-6.5 years). During a mean follow-up time of 9.0± 3.8 years, the incidence rate of autoimmune diseases was 66.5 per 10,000 person-years (95%CI: 64.3-68.8) in the exposed cohort and 52.3 per 10,000 person-years (95%CI: 51.7-52.9) in the unexposed cohort, corresponding to an absolute rate of difference of 14.3 per 10,000 person-years (95%CI: 11.9-16.6). Children in the exposed cohort had an increased risk of autoimmune disease (HR: 1.26; 95%CI: 1.21-1.31) and this association was similar in the separate analysis of hospital databases (HR: 1.25; 95%CI 1.06-1.49). 4 Conclusion: M. pneumoniae infection requiring hospitalization may be associated with an increase in subsequent diagnoses of autoimmune diseases.